Optimization of the extraction process and molecular mechanism of inhibition on tyrosinase of kojic acid - FANG Jingjie; CHEN Jian; CHEN Yajuan; LIANG Ying (Shipin yu jixie, 2024)
Objective: This study aimed to develop new, efficient, safe and precise tyrosinase inhibitors. Methods: The orthogonal test was used to optimize the extraction conditions of kojic acid. The inhibitory effect of kojic acid on tyrosinase was studied by enzyme kinetics, and the mechanism of its interaction with tyrosinase from different sources was analyzed by molecular docking technology. Results: The optimum process conditions for extracting kojic acid were as follows: activated carbon content of 5%, decolorization temperature of 75 ℃, pH 2.0, decolorization time of 50 min, and the purity of kojic acid was 97.85%. the IC50 of kojic acid on tyrosinase monophenolase and tyrosinase bisphenolase were 13.33 and 53.32 μg/mL, respectively. The XP docking scores of kojic acid with mushroom, mouse, gorilla, and human tyrosinase were -7.515, -5.011, -5.537, and -3.638, respectively. The results of MM-GBSA were 94.47, -110.80, -1.17 and 6.45 kJ/mol, respectively. Conclusion: Under the control of the optimal process conditions, the purity of kojic acid can be significantly improved. Kojic acid has a competitive inhibitory effect on tyrosinase. Tyrosinase from different sources combines with kojic acid to form different types of non-covalent bonds, the binding stability of the inhibitor and different tyrosines is different.